New species of oribatid mites of the family Oppiidae (Acari, Oribatida) from Chile - Ermilov, Sergey G. (Zootaxa, 2019)
Three new species of oribatid mites (Oribatida) of the family Oppiidae collected from swamp moss near Laguna Parrillar National Park in Chile (Patagonia) are described. Kokoppia lagunaensis sp. nov. differs from Kokoppia inclinata, K. rafalskii and K. pectinata by the following morphological traits: body size; structure of costulae; absence of transcostula; presence of interbothridial tubercles; morphology of bothridial setae; number of solenidia on leg tarsi II. Setoppia parrillarensis sp. nov. differs from Setoppia strinovichi by the following morphological traits: body size; length of interlamellar setae; localization of notogastral setae la and adanal lyrifissures; absence of costulae. Graptoppia (Stenoppia) magallanesensis sp. nov. differs from Graptoppia (Stenoppia) italica by the following morphological traits: absence of transcostula; localization of notogastral setae la; presence of interbothridial tubercles. The species Oppia inclinata Hammer, 1962 is transferred to the genus Kokoppia and now is given as Kokoppia inclinata (Hammer, 1962) comb. nov.